Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Keo San Indonesia - Sifah Fauziah (2021)
This research is a quantitative study that aims to determine and prove the effect of work environment and work discipline on employee performance. The sample used in this study were all employees of the production section of PT Keo San Indonesia where the researchers used a saturated sample of 60 employees. Data collection is done via google form. The analytical technique used is the path analysis method and data processing is carried out through SmartPLS 3.3.3. The results of the test obtained (1) the work environment has a significant effect on employee performance, (2) work discipline has a significant effect on employee performance. Keywords: work environment, work discipline, and employee performance.